Impact of physical exercise habit on career decision-making behavior in college students: a chain mediating effect of self-efficacy and psychological resilience - Niu, Chuanjie; Jiaxin, Deng; Liu, Yongfeng (Frontiers in Psychology, 2025)
ObjectiveTo explore the mechanism through which physical exercise habits influence college students' career decision-making behavior, and to verify the independent and chain mediation effects of self-efficacy and psychological resilience within this relationship.MethodsUsing stratified random sampling, questionnaires were distributed to universities students across China, and valid questionnaires were collected. The Physical Activity Rating Scale (PARS-3), General Self-Efficacy Scale (GSES), Connor-Davidson Resilience Scale (CD-RISC-10), and Career Decision-Making Difficulty Scale (CDMP) were employed. Structural equation modeling and the Bootstrap method were used to test the chain mediation effect.ResultsPhysical exercise habits significantly and positively influenced career decision-making ability. Both self-efficacy and psychological resilience served as independent mediators. The chain mediation path from self-efficacy to psychological resilience was significant. The mediation effects accounted for 39.6% of the total effect.ConclusionPhysical exercise significantly and positively influences career decision-making behavior by enhancing self-efficacy and psychological resilience, with self-efficacy and psychological resilience forming a chain transmission mechanism.